2007
DOI: 10.1128/jcm.01100-07
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Helicobacter Species, “ Helicobacter macacae ,” from Rhesus Monkeys with and without Chronic Idiopathic Colitis

Abstract: Chronic idiopathic colitis is a common clinical entity in young captive rhesus monkeys. Eight isolates, cultured from five monkeys in colony 1 with endemic diarrhea and three from colony 2 without diarrhea, were grown under microaerobic conditions on selective agar and were classified by full 16S rRNA sequence, biochemical, and phenotypic analysis as a novel helicobacter, "Helicobacter macacae" (proposed name). All eight strains of H. macacae had 99.5% identical 16S rRNA sequences.Chronic idiopathic colitis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 13 publications
0
35
1
1
Order By: Relevance
“…Other putative species detected in the present study include 'H. macacae', previously isolated from rhesus monkeys with and without chronic idiopathic colitis (Fox et al, 2007), H. pullorum and H. canadensis, as well as several species mainly detected in rodents, such as H. trogontum (only detected in unhabituated animals), H. rodentium, H. ganmani, H. mesocricetorum, H. mastomyrinus and H. typhlonius. In addition to H. cinaedi and H. fennelliae, several of these species (H. rodentium, H. canadensis, H. pullorum) have been associated with diarrhoea, colitis or chronic liver diseases in humans (Fox et al, 2000;Ceelen et al, 2005;Nakonieczna et al, 2010;Hansen et al, 2011).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Other putative species detected in the present study include 'H. macacae', previously isolated from rhesus monkeys with and without chronic idiopathic colitis (Fox et al, 2007), H. pullorum and H. canadensis, as well as several species mainly detected in rodents, such as H. trogontum (only detected in unhabituated animals), H. rodentium, H. ganmani, H. mesocricetorum, H. mastomyrinus and H. typhlonius. In addition to H. cinaedi and H. fennelliae, several of these species (H. rodentium, H. canadensis, H. pullorum) have been associated with diarrhoea, colitis or chronic liver diseases in humans (Fox et al, 2000;Ceelen et al, 2005;Nakonieczna et al, 2010;Hansen et al, 2011).…”
Section: Discussionmentioning
confidence: 61%
“…Apart from humans, members of the genus Helicobacter have also been detected in a wide variety of other animal species, both domesticated and non-domesticated (Fox et al, 2007;Haesebrouck et al, 2009;Schrenzel et al, 2010;Lertpiriyapong et al, 2014). These include various non-human primates, such as rhesus macaques, mandrills and crab-eating macaques (O'Rourke et al, 2004;Schrenzel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Natural EHS infection has also been associated with colitis and intestinal adenocarcinoma in non-human primates. In rhesus macaques, EHS were commonly cultured in rhesus with chronic colitis, with a 81 % prevalence among primates with diarrhoea and 57 % prevalence in a non-diarrheic cohort housed in different institutions (Fox et al, 2007. Subsequent studies have identified persistent infection and 93 % EHS prevalence among rhesus macaques with intestinal adenocarcinoma (IAC) (Marini et al, 2010;Lertpiriyapong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…H. hepaticus, H. bilis, and other EHS infections in immunocompromised mice cause chronic typhlocolitis, high-grade dysplasia, and progression to colitis-associated carcinoma (CAC) (8)(9)(10)(11). Novel Helicobacter spp., including H. macacae, have been cultured from idiopathic colitis and colon adenocarcinomas in rhesus monkeys (12)(13)(14). H. cinaedi and H. fennelliae were first isolated from homosexual men (presumably immunocompromised by HIV infection) with proctitis (15).…”
mentioning
confidence: 99%